Green Synthesis, Structural Characterization and Study of Thermal Behaviour of Cu2+ and Co2+ Complexes Derived from Salicylidene-3-Amino Benzoic Acid - O, Ama S.; A, Wuana R.; R, Sha’ato; S, Eneji I. (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2024)
The Schiff base ligand Salicylidene-3-amino benzoic acid (SAB) was prepared by reacting salicylaldehyde with 3-amino benzoic acid. Its Cu2+ and Co2+ complexes were prepared by reacting ethanolic solutions of SAB with magnetically stirred solution of metal salts in distilled water using microwave-assisted heating for 30 min. The ligand and complexes were characterized on the basis of physical properties, FT-IR, UV-Vis, magnetic susceptibility, XRD and TGA/DTA. Unit cell dimensions obtained from XRD crystallography analysis agreed with the establishment of orthorhombic crystal structure. The spectroscopic studies revealed the presence of -C=N, -C=O, M-O, M-N, -OH and NO3 functional groups and this showed that the ligand coordinated to metal via N and O donors. The thermal decomposition of the complexes indicates the loss of lattice of water and decomposition of the ligand as key to the interpretation of successive weight loss.